Вміст поживних речовин та енергетична цінність рослинної сировини генотипів свічграсу (Panicum virgatum L.) - Vergun, O.M.; Rakhmetov, D.B.; Rakhmetova, S.O.; Fishchenko, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2018)
Objective – to investigate biochemical properties of plant raw material of 1 cultivar and 14 varieties of Panicum virgatum L. in conditions of M.M. Gryshko National Botanical Garden of the NAS of Ukraine. Material and methods. Investigated plants were 1 cultivar and 14 varieties of Panicum virgatum collected in an experimental collection of Cultural Flora Department of National Botanical Garden of the NAS of Ukraine: Panicum virgatum f. DB (PVDB), P. virgatum f. DN (PVDN), P. virgatum f. PL (PVPL), P. virgatum f. PN1 (PVPN1), P. virgatum f. PN2 (PVPN2), P. virgatum f. PN3 (PVPN3), P. virgatum f. PB (PVPB), P. virgatum f. PP (PVPP), P. virgatum f. RL (PVRL), P. virgatum f. RR (PVRR), P. virgatum f. SL1 (PVSL1), P. virgatum f. SL2 (PVSL2), P. virgatum f. VP (PVVP), P. virgatum f. VR (PVVR), P. virgatum cv. Zoriane (PVZ). The content of dry matter was determined according to A.I. Yermakov, the total content of sugars, monosaccharides and ascorbic acid concentration – according to V.P. Krishchenko, the content of carotene – according to B.P. Pleshkov, the content of ash – according to Z.M. Hrycaenko. Energetic value of dry plant raw material measured on calorimeter IKA200. The content of photosynthetic pigments in leaves detected according to M.M. Musienko on spectrophotometer Unico UV 2800. Results. In the period of anthesis the plant raw material of Panicum virgatum accumulated dry matter from 34.05 % (PVZ) to 48.21 % (PVPL), monosaccharides – from 2.68 % (PVSL2) to 5.92 % (PVPN2), ascorbic acid – from 14.39 mg% (PVRL) to 79.50 mg% (PVSL1), carotene – from 0.277 mg% (PVPB) to 1.407 mg% (PVSL2), ash – from 1.88 % (PVVR) to 4.63 % (PVPN1) and total content of sugars – from 4.11 % (PVSL2) to 10.49 % (PVPN2). The calorific value of dry raw was from 3588.18 cal/g (PVVR) to 3719.22 cal/g (PVPN1). The ratio of photosynthetic pigments content was 1.09 (PVPN3) – 5.01 (PVPP), the ratio of the sum of chlorophylls to carotenoids content – from 2.47 (PVSL2) to 9.30 (PVPD). Conclusions. Obtained data demonstrated that in conditions of M.M. Gryshko National Botanical Garden of the NAS of Ukraine cultivar and varieties of Panicum virgatum are the valuable source of nutrients in the period of anthesis. Among investigated plants the PVPL genotype characterized by the most content of dry matter and chlorophyll b, PVPN2 – total content of sugars and monosaccharides, PVSL1 – ascorbic acid, PVSL2 – carotene, PVPN1 – ash and calorific value, PVPP – chlorophyll a and ratio of chlorophylls, PVPN3 – carotenoids.